Interdisciplinary research: putting the methods under the microscope - Robertson, David W (BioMed Central, 2003)
BACKGROUND: While the desirability of interdisciplinary inquiry has been widely acknowledged, indeed has become 'the mantra of science policy', the methods of interdisciplinary collaboration are opaque to outsiders and generally remain undescribed. DISCUSSION: Many have analysed interdisciplinarity, especially in relation to the creation of new disciplines and institutions. These analyses are briefly outlined. Still, there currently persists a silence about the methods of interdisciplinary collaboration itself, and the core of this paper proposes a template for such methods. SUMMARY: Breaking this silence – by making the methods of interdisciplinary projects transparent – could further invigorate interdisciplinary research.